2023
DOI: 10.3389/fmicb.2023.1130594
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of psychrophilic enzymes using machine learning algorithms with amino acid composition descriptor

Abstract: IntroductionPsychrophilic enzymes are a class of macromolecules with high catalytic activity at low temperatures. Cold-active enzymes possessing eco-friendly and cost-effective properties, are of huge potential application in detergent, textiles, environmental remediation, pharmaceutical as well as food industry. Compared with the time-consuming and labor-intensive experiments, computational modeling especially the machine learning (ML) algorithm is a high-throughput screening tool to identify psychrophilic en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Previous studies have also reported that cold‐adapted serine hydroxymethyl transferase enhanced the interaction with solvents to improve their conformational flexibility, which resulted in high catalytic activity at low temperatures (Zhang, Xia, et al, 2021). In addition, statistical analyses of amino acids of the psychrophilic and mesophilic proteins showed that there are more Ser and Thr amino acids in the psychrophilic proteins, which lead to the formation of more interactions between the proteins and water molecules, thus increasing the flexibility of protein structure (Huang et al, 2023; Nath & Subbiah, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have also reported that cold‐adapted serine hydroxymethyl transferase enhanced the interaction with solvents to improve their conformational flexibility, which resulted in high catalytic activity at low temperatures (Zhang, Xia, et al, 2021). In addition, statistical analyses of amino acids of the psychrophilic and mesophilic proteins showed that there are more Ser and Thr amino acids in the psychrophilic proteins, which lead to the formation of more interactions between the proteins and water molecules, thus increasing the flexibility of protein structure (Huang et al, 2023; Nath & Subbiah, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, studies based on machine learning have been reported on thermophilic and mesophilic bacterial proteins, however little is known about the application of ML approach in psychrophilic enzymes. Recent study on psychrophilic amino acid composition (AAC) using machine learning (ML) algorithm showed that psychrophiles proteins contains high frequency of Ala, Gly, Ser, and Thr, compared to Glu, Lys, Arg, Ile, Val, and Leu amino acids (Huang et al, 2023a). The support vector machine learning model (SVM) in combination with molecular dynamics (MD) is employed to study the thermostability of psychrophilic alpha-amylase (Figure 3) (exhibited high activity at low temperature) isolated from Pseudoalteromonas haloplanktis (Li et al, 2020).…”
Section: Machine Learning Approachmentioning
confidence: 99%
“…It was shown that proteins adapted to different temperatures are highly similar, that no alterations in the reaction mechanism are involved, that all catalytic residues are highly conserved (see Figure 4 for an example), and that the structural changes necessary for cold-adaptation are discrete and enzyme-specific [58]. As compared to enzymes adapted to higher temperatures, cold-adapted enzymes frequently display a reduction in strength and/or number of stabilizing interactions, and/or an introduction of specific protein flexibility-enhancing modifications [32,[59][60][61][62]. These alterations may be localized, commonly near the active site, or global.…”
Section: Structural Origins Of Cold-adaptationmentioning
confidence: 99%